Sacraliser le territoire américain : Mount Shasta, quand les dieux viennent instruire les humains - Bernadette Rigal-Cellard (Anglophonia)
This paper focuses on the origins of the significance of Mount Shasta for the Theosophist movements in America. It first presents the major text of the Atlantis canon, A Dweller on Two Planets, or the Dividing of the Way, by Phylos the Thibetan, alias Frederick S. Oliver, and in particular the second part "Seven Shasta Scenes " which narrates how a wise man led the narrator into the wonderful depths of the Mount to introduce him to a fraternity of higher spirits, the Lothins. Then, we look at a famous book Unveiled Mysteries, by Godfre Ray King, alias Guy Ballard, the founder of the I AM cult, who obviously got his inspiration from the first Shasta novel. Ballard replaces the Lothin fraternity with the Great White Brotherhood, a gathering of perfected humans who have deified themselves and come to Mount Shasta to teach humans how to reach the same level of enlightenment, Saint Germain being Godfre’s guide among those Ascended Masters. Ballard belongs to the old esoteric tradition that Helena Petrovna Blavatsky would popularize at about the same time Oliver’s book was written. We then briefly present one of the scions of I AM, the Summit Lighthouse, or Church Universal and Triumphant, its belief in the Ascended Masters communicating from Mount Shasta and finally from the Teton. In these books and religious movements those mountains are not viewed as metaphorically representing transcendence and spirituality, but they truly are the residence of those higher powers. Mount Shasta in particular is still one of the most popular power spots of New Agers who regularly convene on its slopes to await final liberation